Clostridioides difficile: innovations in target discovery and potential for therapeutic success. - Monaghan,TM; Seekatz,AM; Mullish,BH; Moore-Gillon,CCER; Dawson,LF; Ahmed,A; Kao,D; Chan,WC (Expert Opin Ther Targets, 2021)
INTRODUCTION: Clostridioides difficile infection (CDI) remains a worldwide clinical problem. Increased incidence of primary infection, occurrence of hypertoxigenic ribotypes, and more frequent occurrence of drug resistant, recurrent, and non-hospital CDI, emphasizes the urgent unmet need of discovering new therapeutic targets. AREAS COVERED: We searched PubMed and Web of Science databases for articles identifying novel therapeutic targets or treatments for C. difficile from 2001 to 2021. We present an updated review on current preclinical efforts on designing inhibitory compounds against these drug targets and indicate how these could become the focus of future therapeutic approaches. We also evaluate the increasing exploitability of gut microbial-derived metabolites and host-derived therapeutics targeting VEGF-A, immune targets and pathways, ion transporters, and microRNAs as anti-C. difficile therapeutics, which have yet to reach clinical trials. Our review also highlights the therapeutic potential of re-purposing currently available agents . We conclude by considering translational hurdles and possible strategies to mitigate these problems. EXPERT OPINION: Considerable progress has been made in the development of new anti-CDI drug candidates. Nevertheless, a greater comprehension of CDI pathogenesis and host-microbe interactions is beginning to uncover potential novel therapeutic targets, which can be exploited to plug gaps in the CDI drug discovery pipeline.